Toxicological and Physiological Effects of DDT on Caenorhabditis elegans - Mahmood, S.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
Toxicity assays were used in this study to test how DDT affects lethality and brood size of Caenorhabditis elegans (C.elegans) by exposing them to various concentrations of this agent. These nematodes have provided a very informative system that was utilized to study the behavioural and physiological processes. The results showed that DDT affected the lethality in a dose-dependent manner, but 100% kill was not achieved with concentration tested. Whereas, sodium azide, positive control does have an effect on C. elegans and significantly inhibiting lethality (LC50 0.01mM). Similarly, DDT led to a pronounced effect in brood size of C.elegans compared to the mean brood size recorded for the control (0.1% DMSO). Sodium azide results showed a greater difference in brood size compared to DDT. Both agents, DDT and sodium azide caused a remarkable inhibitory effect on C.elegans pharyngeal pumping rate. It can be concluded that the target site of DDT in C.elegans might not be the same target in insect.